Response of maize (Zea mays) to different planting methods with limited irrigation at water sensitive growth stages - KAUR, RAMANJIT; KUMAR, SUNIL; DAS, ANCHAL; SINGH, TEEKAM; KUMAR, PRAVEEN; DAWAR, RAKESH (The Indian Journal of Agricultural Sciences, 2023)
In Indo-Gangetic Plains, ground water is the main source of irrigation. Maize (Zea mays L.) is the main rainy (kharif) season crop of the region after rice (Oryza sativa L.) and it is quite exhaustive crop in terms of nutrients and water as well. For efficient utilization of resources like nutrients and water and for maintaining sustainable yield at the same time of maize crop we need some agronomic alternatives. From the various alternatives, one promising alternative is by modifying the planting system along with limited water application at critical stages of crop. So by keeping all this in view, a field experiment was conducted to study the response of maize to bed system of planting with limited irrigation at water sensitive growth stages during 2017 and 2018 at ICAR-Indian Agricultural Research Institute, New Delhi. The experiment was laid out in a factorial randomized complete block design (FRCBD) with two crop establishment methods, i.e. narrow bed and broad bed planting and 5 levels of irrigation with 3 replications. Significantly higher grain yield was recorded in broad bed system of planting (4.37 and 4.57 t/ha) compared with narrow bed (4.23 and 4.38 t/ha) during 2017 and 2018, respectively. The highest grain yield was recorded where irrigation was applied at 25% depletion of available soil moisture (4.86 and 4.93 t/ha). It was concluded that sowing of maize on broad beds with irrigation in furrows at 25% depletion of available soil moisture resulted in higher growth, yield attributes and yield of maize compared to rest of the treatments.